UPAYA PERAN PENYIDIK SAT NARKOBA DALAM PENANGANAN PENYALAHGUNAAN NARKOBA DI WILAYAH HUKUM POLRES KUTAI TIMUR - Chresna Rivan (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACT The drug problem is a national and international problem, because its abuse will negatively impact the lives of the people, nation and state. The development trend of drug crimes in Indonesia recently showed a very sharp increase. One of the results of the National Police's analysis of the high crime rate is one of which is caused by the economic crisis that has hit almost all regions in the republic. With this incident, producers, distributors and consumers take advantage of this situation to enlarge and seek profits in the distribution and abuse of drugs. In its implementation, the police itself has placed drugs as a case of serious attention and priority, but the tough task certainly will not succeed without the support of all elements of society. The role of the police in tackling drug crime is not only focused on law enforcement alone but also on all efforts shown to reduce the demand and illicit drug needs. In the area of East Kutai itself, especially the Narcotics case up to July 2018, it has surpassed the Narcotics case in 2017.